High School Vocational Counseling Role in Leveraging Students' Professional Inclinations - Gabriel Bratucu; Anca Madar; Nicoleta Andreea Neacsu; Dana Boscor (Amfiteatru Economic Journal, 2014)
The experience of many countries with a well-educated workforce highlights the important role of vocational counselling services for advantageous youth professional orientation. Researchers manifest in their turn, a growing interest to study the role of vocational counselling, from the perspective of increasing the efficiency of investment in education and strengthening the capacity of enterprises to meet the challenges of the knowledge economy.
Keywords: I29; I20; J23; 330; vocational counselling; professional skills; professional career; professional education